Role of Serum Alanine Aminotransferase Aspartate Aminotransferase and Alkaline Phosphatase in Early Detection of Protein Energy Malnutrition - Karmacharya, K; Islam, MN (Journal of Nepal Paediatric Society, 2009)
<!--[if gte mso 9]> mother 11.6568 <![endif]--><!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Objective: Although Protein Energy Malnutrition (PEM) has been studied extensively; the best criteria for its detection in early stages have not been established. This study was carried out to observe the change in transaminases, alkaline phosphatase levels when compared with control and also to see their relationships with various grades of PEM. Then to see if certain biochemical parameters could be used to detect malnutrition in early stage. Methods: Cross sectional study between Jan 1999-Dec 2000,124 children from 5 months to 5 years were included in the study. Out of 124 children 98 (79%) were cases and 26 (21%) normal age matched healthy controls. Cases were divided into groups as per Gomez classification (Group 1-Grade I PEM, 37;Group 2- Grade II PEM, 34; Group 3- Grade III PEM27; and Group 4 26 Healthy controls). Three serum enzymes, Alanine aminotransferase (ALT), Aspartate aminotransferase (AST) and Alkaline Phosphatase (ALP) was analyzed and for statistical analysis student's "t" test was used. Results: The mean serum values +SD of ALT (Grade I PEM-41.40 +13.25,Grade II PEM-31.53+10.6,GradeIIIPEM-33.77+12.45,Control-23.11+8.73) and Aspartate aminotransferase (Grade I PEM-42.8+11.06,Grade II PEM 31.47+8.32,GradeIII PEM 35.00+10.86, Control-25.42+8.77) in patients with PEM were significantly (p <. 0.001) higher than controls. The degree of increase in serum values of these two enzymes was maximum in cases with Grade I PEM. The mean serum values of Alkaline phosphatase (Grade I PEM-403.40+100.76, Grade II PEM-294.23+50.40,Grade III PEM-221.26+94.09,Control-894.5+ 126.28) in cases of PEM were significantly lower than controls, lowering being maximum in PEM Grade III. Conclusion: It can be concluded that abnormalities in blood levels of these enzymes occur in any form of PEM and these are related to the severity of the disease. Hence this may be helpful in early diagnosis of PEM where clinical features are equivocal. Key words: Protein Energy Malnutrition, Enzymes, Alanine Aminotransferase, Aspartate aminotransferase, Alkaline phosphatase doi:10.3126/jnps.v27i2.1412 J. Nepal Paediatr. Soc. Vol.27(2) p.68-72